Państwo w sektorze ochrony zdrowia - Łagowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The healthcare sector is a specific area of economic life. It is connected with people’s strong emotional involvement, especially these people who are forced to use its services. Therefore, formulating any theoretical analysis without value judgments is almost impossible.The author tried to prove that, from the economic point of view, medical service belongs to typical private goods, despite the general social belief that the state should address the issue of health care. However, in countries that have a long tradition of state presence in healthcare, it is difficult to deregulate this sector.At the end, it is worth quoting Devera’s idea that healthcare system consumes up to 90% of expenditures on health care and results in only 10% reduction of mortality. In comparison, spending on promotion of healthy lifestyle consumes approximately 1.5% of expenditures on health care but it reduces mortality by around 40%. Similar financial allocations on the protection of natural environment have a potential impact on the reduction of mortality of approximately 20%. Expenditures on human biology amount approximately to 7% and they could reduce mortality of people by around 30%. It may be worth trying to make society aware that their choices have a much greater impact on the environment than it is commonly thought.
Keywords: ekonomia ochrony zdrowia; polityka ochrony zdrowia; dobra publiczne